2016
DOI: 10.1177/2374623816679184
|View full text |Cite
|
Sign up to set email alerts
|

Methodological Considerations for Content Analysis of Sexual Consent Communication in Mainstream Films

Abstract: Young adults and college students who receive limited information about certain facets of sexuality, such as how to initiate sex and communicate consent, may turn to television and film for models. In fact, previous research suggests that young adults seek out media content such as television and film to obtain information about sexuality particularly in the absence of other sources of information. As such, it is important to understand the types of actions and behaviors modeled in mainstream media with regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 36 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…Regarding external sexual consent, feedback provided by pilot participants in their open-ended responses indicated that they struggled to distinguish the various constructs of consent communication. Corroborating this feedback, the strong correlations between verbal and explicit cues as well as between nonverbal and implicit cues suggest that participants may have conflated these types of consent communication in their event-level data – even though they are conceptually distinct categorization systems (Hickman & Muehlenhard, 1999 ; Jozkowski et al, 2016 ). To help clarify these distinctions in future studies, we recommend that researchers using the ESM measure of external sexual consent provide the operational definitions of straightforward, subtle, verbal, and nonverbal signals ( Table 1 ) to participants at the beginning of the study.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Regarding external sexual consent, feedback provided by pilot participants in their open-ended responses indicated that they struggled to distinguish the various constructs of consent communication. Corroborating this feedback, the strong correlations between verbal and explicit cues as well as between nonverbal and implicit cues suggest that participants may have conflated these types of consent communication in their event-level data – even though they are conceptually distinct categorization systems (Hickman & Muehlenhard, 1999 ; Jozkowski et al, 2016 ). To help clarify these distinctions in future studies, we recommend that researchers using the ESM measure of external sexual consent provide the operational definitions of straightforward, subtle, verbal, and nonverbal signals ( Table 1 ) to participants at the beginning of the study.…”
Section: Discussionmentioning
confidence: 92%
“…Jozkowski et al (2014) also developed an External Consent Scale. However, this measure does not directly map onto Hickman and Muehlenhard's (1999) conceptualization of external consent communication, which has been used in several recent studies (e.g., Jozkowski et al, 2016;Willis, Blunt-Vinti et al, 2019). Specifically, Jozkowski et al's (2014) items may be too specific to fully encompass the myriad ways people communicate consent.…”
Section: Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…We coded the open-ended data regarding typical sexual consent communication by drawing on themes from previous research (e.g., Hickman & Muehlenhard, 1999 ; Jozkowski et al., 2016 ). To create the codebook for this question, the first and third authors independently read separate subsamples of the responses (∼25% in total) to identify salient statements that were relevant to the theme of sexual consent communication (Braun & Clarke, 2006 ).…”
Section: Methodsmentioning
confidence: 99%
“…It included: (1) description of the series and episodes, (2) identification of themes belonging to one of the two following groups ‘sexual health themes’ or ‘other health themes’ and (3) qualitative material for sexual health promotion composed of dialogue verbatims and scene descriptions. Our data collection and coding process is near to the methodology developed by Jozkowski et al 31 except that we focused on the episodes as a whole and our coding focused on sexual health promotion messages.…”
Section: Methodsmentioning
confidence: 99%